Management of tillage equipment on research farms - Claassen, S.L. (1995)
The goal of tillage is to provide a suitable environment for seed germination and root growth, and to control weeds. Research on tropical soils has shown that tillage is only useful to control weeds. In general, tillage damages the soil. Chemical weed control is preferable. In many African countries however, herbicides are not available, and conventional tillage will still be necessary. Primary tillage is an aggressive operation that leaves the surface rough, while secondary tillage equipment level and firm the soil.